2007
DOI: 10.1038/nphys729
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized network evolution coupled to extremal dynamics

Abstract: The interplay between topology and dynamics in complex networks is a fundamental but widely unexplored problem. Here, we study this phenomenon on a prototype model in which the network is shaped by a dynamical variable. We couple the dynamics of the Bak-Sneppen evolution model with the rules of the so-called fitness network model for establishing the topology of a network; each vertex is assigned a fitness, and the vertex with minimum fitness and its neighbours are updated in each iteration. At the same time, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 29 publications
2
73
0
Order By: Relevance
“…Different mechanisms may be contributing simultaneously to the evolution of a real-world complex network. The present paper suggested that the interplay between dynamics and structure can be an important driving force for the formation and stabilization of heterogeneous structures which are ubiquitous in biological and social systems [8,10,11,13,14,16,17,18,19]. A lot of efforts are needed to decipher the detailed dynamics-structure coupling mechanisms in many complex systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different mechanisms may be contributing simultaneously to the evolution of a real-world complex network. The present paper suggested that the interplay between dynamics and structure can be an important driving force for the formation and stabilization of heterogeneous structures which are ubiquitous in biological and social systems [8,10,11,13,14,16,17,18,19]. A lot of efforts are needed to decipher the detailed dynamics-structure coupling mechanisms in many complex systems.…”
Section: Discussionmentioning
confidence: 99%
“…The system only needs to accumulate decentralized and local structural changes under the selection of dynamics-structure coupling. Networks with pronounced power-law degree distributions also emerged in other model systems with comparable dynamicl and evolutionary time scales [16,17]. In real-world systems, it was noticed by Aldana [26] that a major fraction of scale-free complex networks has their decay exponent γ in the tiny range of γ ∈ [2.0, 2.5].…”
Section: Dynamics and Evolutionmentioning
confidence: 99%
“…Being so well studied, the Bak-Sneppen model is ideal for studying the effects introduced by a feedback mechanism between fitness dynamics and topological restructuring. For this reason, it is at the basis of the adaptive model [6] that we shall present in detail in section 4.…”
Section: The Bak-sneppen Modelmentioning
confidence: 99%
“…In particular, we shall present a self-organized model [6] where an otherwise static model of network formation driven by vertex fitness [7] is explicitly coupled to an extremal dynamics process [8] providing an evolution rule for the fitness itself. In order to highlight the novel phenomena that originate from the interplay between the two mechanisms, we first review the main properties of the latter when considered separately.…”
Section: Introductionmentioning
confidence: 99%
“…ITN is defined as the network of import-export relationships between world countries in a given period (usually a year). Many efforts have been devoted to analyze the structure and the dynamics of the ITN from an empirical and theoretical modeling perspective (see, for instance, [18][19][20][21][22][23][24][25][26]). In particular, since it is a dense weighted network, it is rather difficult to define a tractable reference case against which one can measure the specific features of the real system.…”
mentioning
confidence: 99%